Distribution of alpha-neoendorphin, ACTH (18-39) and beta-endorphin (1-27) in the alpaca brainstem - Sánchez, Manuel L. (2018)
Using an immunocytochemical technique, we have studied in the alpaca brainstem the distribution of immunoreactive structures containing prodynorphin (alpha-neoendorphin)- and pro-opiomelanocortin (adrenocorticotrophin hormone (18-39) (ACTH), beta-endorphin (1-27))-derived peptides. No peptidergic-immunoreactive cell body was observed. Immunoreactive fibres were widely distributed, although in most of the brainstem nuclei the density of the peptidergic fibres was low or very low. In general, the distribution of the immunoreactive fibres containing the peptides studied was very similar. A close anatomical relationship occurred among the fibres containing alpha-neoendorphin, ACTH or beta-endorphin (1-27), suggesting a functional interaction among the three peptides in many of the brainstem nuclei. The number of fibres belonging to the prodynorphin system was higher than that of the pro-opiomelanocortin system. A moderate/low density of immunoreactive fibres was observed in 65.11% (for alpha-neoendorphin (1-27)), 18.18% (for ACTH) and 13.95% (for beta-endorphin) of the brainstem nuclei/tracts. In the alpaca brainstem, a high density of immunoreactive fibres was not observed. The neuroanatomical distribution of the immunoreactive fibres suggests that the peptides studied are involved in auditory, motor, gastric, feeding, vigilance, stress, respiratory and cardiovascular mechanisms, taste response, sleep-waking cycle and the control of pain transmission.